Los hechos gravados en el IVA en el derecho comparado - Villanueva Gutiérrez, Walker (2014)
This article analyzes the definitions of the main taxable events for the Value-Added Tax (VAT) based on a comparative approach to thelegislation of different countries (Spain, Mexico, Chile, Colombia, Argentina and Peru). In this regard, it analyzes which legislations offer definitions according to the principles of generality, fiscal neutrality and legal certainty for VAT. Moreover, it points out that the VAT systems of those countries do not require as a condition for the configuration of the taxable events that the transactions involve a «value added» or a final consumption. In the specificcase of «supplies of goods», the VAT systems have a similar definition of the taxable event, although there are a few differences. However, in the case of«supplies of services», which is the most important taxable event for VAT, there are important differences at the time each country defines it. This is not a desirable effect for the international trade of services, since the lack of harmonization produces double taxation or double non taxation.